Effect of pyrolysis pressure on activity of Fe–N–C catalysts for oxygen reduction. Issue 43 (8th October 2015) - Gumeci, Cenk; Leonard, Nathaniel; Liu, Yuanchao; McKinney, Samuel; Halevi, Barr; Barton, Scott Calabrese
Abstract : In the synthesis of Fe–N–C catalysts by high-pressure pyrolysis, higher precursor loading increases gas-phase pressure and enhances nitrogen retention, active site density and ORR activity. Abstract : Iron and nitrogen doped carbon, Fe–N–C, catalysts are synthesized by high pressure pyrolysis of Ketjenblack carbon, melamine and iron acetate precursor mixture in a closed, reusable scale-up stainless steel reactor. The effects of precursor loading with constant precursor ratios on obtained pressure, nitrogen retention and oxygen reduction reaction (ORR) activities are studied. The results indicate that higher precursor loading increases the gas phase pressure and improves nitrogen retention and ORR activity. Furthermore, a relationship is found between active site density, nitrogen retention and pressure that suggests that the limiting reaction may be an adsorption process driven via high pressure of volatile intermediates from the melamine.